How Quality of Work-life’s Mediating Effect of Compensation System on Teacher’s Organizational Commitment? - Sulistiasih Sulistiasih; Widodo Widodo (Psychocentrum Review, 2021)
This study analyzes the effect of compensation system on teachers’ organizational commitment mediating by quality of work-life (QWL). The research data was collected by a questionnaire through the survey methods toward 325 teachers of a private school in Indonesia. Data analysis uses path analysis supported by descriptive statistics and correlational. The results show that compensation system had a significant effect on teachers’ organizational commitment mediating by QWL.  This study also was found a fit research model can discuss among researchers and practitioners as references/discourse or a strategy for enhancing organizational commitment in various research fields and contexts.